Hybrid copper halide material with perovskite like structure with tetrahedral units; synthesis, characterization and optical properties. (1st February 2023) - Ioannou, Anna; Anyfantis, George C.; Milonakou-Koufoudaki, Karmen; Danezis, George; Georgiou, Constatinos A.; Psycharis, Vassilis; Raptopoulou, Catherine P.; Kollia, Constantina; Kelaidis, Nikolaos; Lathiotakis, Nektarios N.; Mousdis, George A.
Graphical abstract: Abstract: Many attempts have been made to substitute lead as the metal cation in perovskite materials but, at the same time, retain its favorable optical and electrical properties. Copper is a naturally abundant metal as well as more environmentally friendly than Pb, thus, can be used as the metal cation in regards to possible substitution candidate perovskites. Herein we report the synthesis and optoelectronic properties of two novel compounds with perovskite-like structure and Cu as the central cation. The analysis includes Powder XRD data and a Density Functional Theory (DFT) study for a thorough understanding of their structure. By Inductively Coupled Plasma Mass Spectrometry (ICP-MS), Vibronic studies (FTIR, Raman), Nuclear Magnetic Resonance (NMR) and Mass spectra we fully explain the chemical analysis of the final material. Complete analysis of their optoelectronic properties is explained and presented with UV–vis measurements. Furthermore, we correlate their properties with their structure with Raman spectroscopy but also via computational theoretical DFT studies.